Attitude control of a minihelicopter in hover using different types of control - Aguirre Gil, Iñaki; Barrientos, Antonio; Del Cerro, Jaime (Rev. Téc. Fac. Ing. Univ. Zulia)
Helicopters exhibit highly nonlinear dynamics with strongly coupled modes. They are very difficult to model and to control. In this paper, a model of the minihelicopter in hovering is proposed and controlled using different types of control strategies: a Linear Quadratic Gaussian (LQG), a Pole Placement and a Proportional-Integral-Derivative (PID) one. The controllers are compared using a performance index in order to select the best one. A test platform is proposed in order to perform tests and avoid helicopter crashes and sensor losses. This paper also describes de ELEVA Architecture (Unmannded Aerial Vehicle for the Inspection of Electrical Power Lines), developed in the Departamento de Automática, Ingenieria Electrónica e lnformática Industrial (DISAM) of Universidad Politécnica de Madrid. The ELEVA prototype uses the control strategies presented in the paper.